Vodún/Vodu, resistance, and north/south relations in undemocratic Togo - Montgomery, Eric James (Journal of religion in Africa, 2020)
Abstract Vodún/Vodu have long served as a “way of life” and ontology for making sense of the world along the Bight of Benin, and in the Caribbean and Atlantic world where many slaves were brought. In Togo, the core ethnic groups, the Ewes, continue to turn inward toward Vodún/Vodu traditions as mechanisms of resistance against an autocratic and despotic rule of a northern regime. While the north remains underdeveloped regarding education, economics, and health care delivery—the majority southern Ewes remain locked out of a political process run by the Eyadema regime, who regularly cite north/south conflict as a justification for absolute one-party rule over all of Togo. Vodun/Vodu become motors of modernity through creative assimilation and adaptation to the most pressing geopolitical concerns of the day. This paper assesses the relationship between Vodun/Vodu and contemporary Togolese politics, and its resistance to state-sponsored terror and autocracy.